Task‐based image quality and dosimetric validation of HyperSight CBCT for adaptive radiotherapy - Byungmoon Park; Taeyoon Kim; Kwan‐Woo Lee (Journal of Applied Clinical Medical Physics, 2026)
Abstract Background Cone‐beam computed tomography (CBCT) is increasingly used in adaptive radiotherapy (ART), yet the dosimetric accuracy and image quality of advanced CBCT imaging platforms—such as Halcyon HyperSight 4.0 (HH), which combines an upgraded detector panel with advanced iterative reconstruction, scatter‐correction, and metal‐artifact‐reduction algorithms—remain insufficiently characterized clinically. Purpose To evaluate HH CBCT reconstruction algorithms for ART by assessing image quality, dose accuracy, and in vivo verification using optically stimulated luminescence dosimeters (OSLDs). Methods Task‐based image quality was evaluated with ImQuest per AAPM TG‐233 using a Gammex 464 ACR phantom on three systems: Canon Aquilion Large Bore CT (LB, reference), TrueBeam (TB), and HH. Seven algorithms were compared (LB, TB‐FDK, TB‐iCBCT, HH‐FDK, HH‐iCBCT, HH‐Acuros, HH‐MAR), with d′ (the detectability index, a task‐based image‐quality metric per AAPM TG‐233) derived for four insert materials (polyethylene, acrylic, bone, air). A volumetric modulated arc therapy (VMAT) plan was independently re‐optimized (using identical optimization objectives/constraints as the LB reference plan) on HH‐iCBCT, HH‐Acuros, and HH‐MAR images and verified by portal dosimetry (1%/1 mm gamma), delivered to an Alderson RANDO phantom with dose measured at 15 points (2 clinical target volume [CTV], 7 organ‐at‐risk [OAR], and 6 lung points) using BeO OSLDs and compared to LB (± 5% criterion). Mean d ′ per algorithm was compared to LB via one‐sample t ‐tests ( p < 0.05). Results HH‐iCBCT ( d ′ = 4.70, p = 0.016), HH‐Acuros ( d ′ = 4.61, p = 0.005), and HH‐MAR ( d ′ = 4.71, p = 0.024, numerically highest) showed significant detectability improvement over LB ( d ′ = 4.42), with HH‐iCBCT most consistent across materials. Mean absolute OSLD dose errors were 1.71%, 2.09%, and 2.90%; all 15 points met the ± 5% criterion except Lt_lung2 in HH‐MAR (−5.32%). Conclusion HH‐iCBCT demonstrated clinically acceptable image quality and dose accuracy for CBCT‐based ART, supported by in vivo BeO OSLD verification in an anthropomorphic phantom.